Special Delivery: Using iPads and Campus Wi-Fi to Enhance an Existing Campus Document Delivery Service. Issue 1 (1st January 2016) - Litsey, Ryan; DeVet, Katherine E.
ABSTRACT: When considering the creation and deployment of new library services, it is important to consider how those services will integrate with existing library workflows. This is especially important when we examine the development or improvement of a campus delivery service for interlibrary loan. Developing such a service as a standalone system outside of the existing document delivery functions is not always the best practice for helping patrons understand how their items will be delivered. On the other hand, endeavoring to integrate such a system into the existing workflow using new types of technology can help bring clarity and efficiency to an already functioning delivery system.